Capsaicinoids and volatile flavor compounds profile of Sichuan hotpot as affected by cultivar of chili peppers during processing. (March 2023) - Yu, Jiao; Zhang, Yiren; Wang, Qiaojun; Yang, Lixue; Karrar, Emad; Jin, Qingzhe; Zhang, Hui; Wu, Gangcheng; Wang, Xingguo
Graphical abstract: Highlights: EJT had highest color intensity, while SSL had highest capsaicinoids content. TPJ and YDJ hotpot oil were preferred by sensory evaluation. A total of 74 volatile compounds were detected. Aldehydes, ketones, esters, and acids were the dominant volatile compounds. 18 hotpot oils could be well divided into 4 groups by PCA. Abstract: Sichuan hotpot oil is a distinctive traditional Chinese cuisine, and chili pepper is an essential material for its flavor formation. In this study, the effect of chili pepper cultivars on capsaicinoids as well as Sichuan hotpot oil volatile compounds were examined. Gas chromatography-mass spectrometry (GC–MS) and chemometrics were employed to ascertain the differences between volatile components and flavor. The results showed that the EJT hotpot oil had the highest color intensity of 34.8, and the SSL hotpot oil had the highest capsaicinoids content of 1.536 g/kg. The results of QDA showed distinct differences among hotpot oils in terms of all sensory properties. A total of 74 volatile components were detected. Aldehydes, ketones, esters, and acids were the dominant volatile compounds formed in 18 hotpot oil samples and showed a significant difference, suggesting that they played a key role in flavor contribution and distinguishing the flavor differences between different hotpot oils. The PCA results well distinguished 18 kinds of hotpot oil.